Pornografi dan Dampak Moral : Suatu Kajian Teologis Mengenai Dampak Negatif dari Pornografi Terhadap Moral Anak Remaja Umur 12-16 Tahun di Pulau Sibandang dan Upaya Gereja untuk Memberikan Solusinya - Anton Sitorus; Ibelala Gea; Rogate Artaida Tiarasi Gultom (Berkat : Jurnal Pendidikan Agama dan Katolik, 2025)
Every day we often hear pornographic news in the mass media, social media, TV, etc. Moreover, with the existence of Android phones, it is easy to access pornographic things, especially among teenagers. That is why there are many cases of fornication, rape due to the release of the consequences of what they watch. It is inevitable that this does not happen because it has been facilitated by cellphones for every teenager. Those who are not yet old enough to know about sex according to their age, make it too early to learn about sex. Teenagers spend more time with cellphones so that they forget to do their work because they are so engrossed. That is why, in this case, parents need to accompany their children in using gadgets so that they can be controlled later in using their Android phones. We hear and see day by day, cases of sexual harassment occur and are increasing regardless of the place whether it is at home, school, public facilities, even in places that are considered sacred. We can see when we watch TV, underage children are the victims of pornography. Not a few have to deal with the police and end up being looted. Pornographic acts are also clearly shown without wearing clothes. There is no longer a sense of shame and reluctance to show off one's body aura to the media for the sake of a morsel of food that must be risked. No thought is given to the negative impacts of all this. By watching freely, the morals of the young generation are damaged, of course the targets are children, teenagers who are still fragile in their stance. They are still easily tempted by things that smell of porn. Several years ago, the government blocked porn sites but the fact that we see is that there are still those who can access them. We do not know what caused why they can still be accessed easily. Is the government not serious enough in handling this problem? Or is it because of someone's skill in fiddling with how to find the site? We leave that question. Now the most important thing is to fortify ourselves with faith in God, for parents, accompany your children in using Android, provide positive activities at home, etc.